2016
DOI: 10.1016/j.jmpt.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography Comparison of Peroneus Muscle Cross-sectional Area in Subjects With or Without Lateral Ankle Sprains

Abstract: The peroneus longus CSA is reduced in participants with LAS compared with that in participants without LAS. The intraexaminer reliability of the ultrasonography protocol was excellent when quantifying the peroneus brevis and the peroneus longus muscle tissues and acceptable when quantifying connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 41 publications
4
58
3
1
Order By: Relevance
“…The results of the reliability study are in line with previous studies that have also reported ICC and LoA values for some of these structures. 19,36,37 The values for the ligament, tendon, and muscle structures are also in agreement with the available literature. For example, Liu et al 19 reported ATFL thickness of 1.95 ± 0.29 mm for healthy participants, very close to our 1.90 ± 0.16 mm.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the reliability study are in line with previous studies that have also reported ICC and LoA values for some of these structures. 19,36,37 The values for the ligament, tendon, and muscle structures are also in agreement with the available literature. For example, Liu et al 19 reported ATFL thickness of 1.95 ± 0.29 mm for healthy participants, very close to our 1.90 ± 0.16 mm.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the wide variability of methods used to calculate the MCID (Chung et al, 2016), we used a case-control study (Lobo et al, 2016a; Lobo et al, 2016b). Age intervals were not equal by years’ distribution in order to permit a similar number of shoulders in each group (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Student’s t -test for independent samples was used for age and outcomes (anterior deltoid and ECRB PPT, and grip strength) and the sex and age group. The minimum clinical differences of the anterior deltoid and ECRB PPT and grip strength were calculated by subtracting the case group from the control group means according to prior studies (Lobo et al, 2016a; Lobo et al, 2016b). Box plots were used to illustrate PPT and grip strength values from the case and control groups.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the lower limb, a recent study found decreased thickness in the vastus medialis muscle in patients with knee osteoarthritis [5]. Additionally, peroneus longus CSA was reduced in patients with lateral ankle sprains compared with patients without this condition [6]. CSA and thickness of the abductor hallucis and flexor hallucis brevis were reduced in patients with hallux valgus [7].…”
Section: Introductionmentioning
confidence: 99%